COMPARATIVE DESCRIPTION OF ANTIVARROATOSIC EFFICIENCY OF VEGETABLE ACARICIDES IN DIFFERENT PERIODS OF THE YEAR - Лукьянова, Г. А. (Scientific Progress & Innovations, 2013)
The analysis of antivarroatosic efficiency of herbal acaricides (powder of wormwood bitter grass, powder of eucalyptus leaves, smoke of horse-radish root) is conducted in the processing of bee families before the main nectar flow (summer) and before forming of winter club (autumn). Acaricidal processing with the use of vegetable preparations on the basis of wormwood bitter grass, eucalyptus leaves and horse-radish root is low effective at autumn treatment against a varroa invasion. Powder of wormwood bitter grass is an effective environmentally clean mean for a fight with varroatosis before the main сollection of honey. Powder of eucalyptus leaves possesses 55,94±10,21 % by efficiency in the processing of bee families before main сollection of honey. Horse-radish root is low effective for a fight against a varroatosis invasion.